A Concise and Modular Three-Step Synthesis of (S)-Verapamil using an Enantioselective Rhodium-Catalyzed Allylic Alkylation Reaction - Tom, Mai-Jan; Turnbull, Ben W. H.; Evans, P. Andrew (Synthesis, 2020)
A concise and modular asymmetric synthesis of the calcium channel blocker (S)-verapamil is described. This approach employs an enantioselective rhodium-catalyzed allylic alkylation reaction between an α-isopropyl-substituted benzylic nitrile and allyl benzoate to construct the challenging acyclic quaternary stereocenter. The terminal olefin then serves as a convenient synthetic handle for a hydroamination to introduce the phenethylamine moiety, furnishing (S)-verapamil in three steps and 55% overall yield, thus providing the most efficient synthesis of this important pharmaceutical reported to date. Furthermore, given the modular nature of the synthesis, it can be readily modified to prepare structurally related bioactive agents.
Keywords: allylic alkylation; enantioselective; nitrile anion; rhodium catalysis; (S)-verapamil